PELAKSANAAN EKSEKUSI OBJEK JAMINAN FIDUSIA BERDASARKAN TITLE EKSEKUTORIAL - Heriawanto, Benny Krestian (Legality : Jurnal Ilmiah Hukum, 2019)
The existence of collateral institutions is very important for creditors particularly to provide certainty over the fulfillment of their rights. In Indonesia there are several collateral institutions, one of which is fiduciary, as a collateral institution, fiduciaries have advantages and disadvantages, especially in carrying out executions, therefore it is necessary to know how the execution of fiduciary collateral objects, especially executions that are based on executorial titles. This paper is based on normative juridical research, with a legal and conceptual approach. According to the research it can be concluded that based on the provisions of article 30 of the Fiduciary Law, with an executorial title, the creditor is given the right to repossess so that the creditor can directly take the object of fiduciary collateral.